Extending the Technology Acceptance Model (TAM) in E-Commerce: The Impact of AI Awareness, Usability, and Trust on Shopee Adoption - Putri, Finola Fiftem Eka; Very, Jhon (YUME : Journal of Management, 2025)
This study examines the adoption of AI-driven features on the Shopee platform among undergraduate students majoring in Management at UPI YPTK Padang, utilizing the Technology Acceptance Model (TAM) with an extended framework that incorporates Perceived Trust as a moderating variable. A quantitative approach was employed, with 300 respondents selected through purposive sampling, and data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS. The findings indicate that AI Awareness significantly influences Perceived Usefulness and Perceived Ease of Use, which in turn positively impact Attitude Toward Using and Behavioral Intention to Use AI-based features. While Behavioral Intention to Use did not significantly predict Actual System Use, Perceived Trust demonstrated a strong direct effect on Actual System Use and moderated the relationship between Behavioral Intention and Actual Use, reinforcing the crucial role of trust in AI adoption. These results suggest that while ease of use and perceived benefits drive AI acceptance, trust remains a fundamental enabler in ensuring consistent engagement with AI-driven e-commerce services. The study highlights the need for enhanced transparency, security, and user education to bridge the gap between behavioral intention and actual adoption. Future research should explore external barriers, risk perceptions, and user demographics to further refine AI adoption models in digital commerce. Keywords: Technology Acceptance Model (TAM), AI Awareness,  Perceived Trust, Shopee.